SEVERAL VOICES, ONE CRIME. CENSORSHIP, IMAGINARIES AND FREEDOMS IN THE CHILEAN PRESS IN DICTATORSHIP FROM THE CASE OF LUMI VIDELA (1974) - Sallusti Palma, Leone Paolo (Revista de Historia Social y de las Mentalidades, 2022)
In the early morning of November 3rd, 1974, the body of Lumi Videla was found dead in the gardens of the Italian Embassy. Around it, the press constructed different theories as to the reason for her assassination. All of them, we know today, were false. However, and in a climate of information censorship, it is worth asking ourselves how was this possible? Why do we find different versions of the same news? This article aims to show how, during the dictatorship, information was not always constructed based on a static work, but at times the media was given an ’imagined freedom’. This, in order to rethink, from this journalistic setup, how media censorship worked in the early years of the Chilean regime.